Effects of transcranial magnetic stimulation on anhedonia in treatment resistant major depressive disorder. Issue 9 (28th August 2021) - Fukuda, Andrew M.; Kang, Jee Won Diane; Gobin, Asi Polly; Tirrell, Eric; Kokdere, Fatih; Carpenter, Linda L.
Abstract: Background: Anhedonia is one of the defining features of depression but it remains difficult to target and treat. Transcranial magnetic stimulation (TMS) is a proven treatment for depression, but its effects on anhedonia and whether anhedonia can be used as a predictive biomarker of response is not well known. Methods: Snaith–Hamilton Pleasure Scale was administered to patients with depression before and after a standard course of TMS in a naturalistic outpatient setting. Results: 144 patients were analyzed. There was an overall significant improvement in anhedonia from pre‐ to post‐treatment (7.69 ± 3.88 vs. 2.96 ± 3.45; p  < .001). Significant correlations between improvements in anhedonia and other depressive symptoms were present ( r  = 0.55, p  < .001). Logistic regression revealed that baseline anhedonia severity was not a significant predictor of clinical outcome. Conclusion: This is the first large, naturalistic study examining the effects of standard, non‐research TMS on anhedonia. Among depressed patients, TMS resulted in significant improvements in anhedonia. Patients with severe baseline anhedonia had an equal chance of achieving clinical response/remission. Patients with anhedonia should not be excluded from treatment if they are safe for outpatient care and otherwise appropriate candidates for treatment. Abstract : Here, we report our findings on the decrease in anhedonia symptoms in patients with treatment resistant depression receiving repetitive transcranial magnetic stimulation (TMS) in a naturalistic outpatient setting. The anhedonia symptoms were measured using a well validated self‐report tool specific for anhedonia: the Snaith–Hamilton Pleasure Scale. Furthermore, we report that baseline anhedonia symptoms and severity were not predictive of clinical outcome of TMS and those with severe anhedonia were just as likely to achieve clinical response/remission.